EXAMPLE NON-EXAMPLE METHOD FOR IMPROVING STUDENTS' WRITING DESCRIPTIVE TEXT - Rahayuni Andyka Putri Situmorang; Fenty D Napitupulu; Usman Sidabutar; Nissi Wuntari Sinaga; Benedictus William Naingolan; Supriandi Sihotang (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This study aims to improve students' ability to write an essay in the descriptive text genre. Descriptive text is a genre that serves to explain something to the reader through writing. To make it easier for researchers to conduct research, researchers use the CAR (Classroom Action Research) method to make it easier for researchers to be closer to the sample. The sample in this study were students of SMPN 5 Percut Sei Tuan with a total of 30 students. Researchers have conducted research with five meetings in four stages, namely planning, and observing. action, and reflection. Quantitative and Qualitative data are tools used in collecting data. Quantitatively, the value of the students' descriptive text is as data, which has been carried out in two cycles. Started the pre-test with a total score of 1953,3 with an average of 64.5. In the first cycle, the total score was 2204.05 with an average of 73.4. The researcher again conducted a post-test in the second cycle to achieve the requirements for teaching success, namely 85%. In cycle 2 the total score was 2621.6 with an average of 87.3. This proves that there is a significant change in student scores using the example non-example method. Qualitative data taken from observation sheets, interviews, and writer's diaries show that it is easier for students to understand teaching and can attract students' attention with an image applicator that guides students to write an essay.